2020
DOI: 10.34172/apb.2021.025
|View full text |Cite
|
Sign up to set email alerts
|

Main Approaches to Enhance Radiosensitization in Cancer Cells by Nanoparticles: A Systematic Review

Abstract: In recent years, high atomic number nanoparticles (NPs) have emerged as promising radio-enhancer agents for cancer radiation therapy due to their unique properties. Multi-disciplinary studies have demonstrated the potential of NPs-based radio-sensitizers to improve cancer therapy and tumor control at cellular and molecular levels. However, studies have shown that the dose enhancement effect of the NPs depends on the beam energy, NPs type, NPs size, NPs concentration, cell lines, and NPs delivery system. It has… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
11
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(13 citation statements)
references
References 135 publications
1
11
0
Order By: Relevance
“…The degree of damage induced by ROS can be determined based on the amount and type of ROS produced, and the exposure duration to ROS. 32 After the induction of the high amount of ROS, it can trigger the cell cycle redistribution and cellular apoptosis. The presence of radiosensitizers in the cancer cells could increase ROS generation.…”
Section: Resultsmentioning
confidence: 99%
“…The degree of damage induced by ROS can be determined based on the amount and type of ROS produced, and the exposure duration to ROS. 32 After the induction of the high amount of ROS, it can trigger the cell cycle redistribution and cellular apoptosis. The presence of radiosensitizers in the cancer cells could increase ROS generation.…”
Section: Resultsmentioning
confidence: 99%
“…For UiO-type nMOFs, each SBU is surrounded by twelve SBUs. [55] The occupation ratio (R SBU ) can be described by Equation (5).…”
Section: Proposed Mechanism For the Radiosensitization Enhancement Of...mentioning
confidence: 99%
“…[3] To increase the ratio of treatment responses to side effects, radiosensitizers have been explored for their ability to preferentially sensitize tumors to ionizing radiation. [4,5] In 1984, Matsudaira et al first demonstrated enhanced cytotoxic effects of radiation in the presence of iodine, [6] spurring intense interest in high-Z element-based radiosensitizers. As indicated by Equation (1), attenuation coefficient (µ) is positively correlated to atomic number (Z) and density (ρ).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In Auger electron therapy, nanoparticles are primarily used as sensitizers for external beam radiation (the interaction of photons with high-Z nanoparticles, resulting in the emission of low-energy and short-range conversion and Auger electrons, which in turn increase the dose deposited in tissues) or as carriers for the delivery of Auger radiation emitters. Since the use of high-Z element nanostructures as sensitizers has been described in many review articles [27][28][29][30][31], we have limited our review only to radiobioconjugates where nanostructures are used as carriers for Auger electron emitters or as radionuclide carriers that induce the emission of photoelectrons from the nanoparticle surface.…”
Section: Introductionmentioning
confidence: 99%